Periodontal disease and some adverse perinatal outcomes in a cohort of low risk pregnant women - Vogt, Marianna (BioMed Central, 2010)
OBJECTIVE: To evaluate the association of periodontal disease (PD) in pregnancy with some adverse perinatal outcomes. METHOD: This cohort study included 327 pregnant women divided in groups with or without PD. Indexes of plaque and gingival bleeding on probing, probing pocket depth, clinical attachment level and gingival recession were evaluated at one periodontal examination below 32 weeks of gestation. The rates of preterm birth (PTB), low birth weight (LBW), small for gestational age (SGA) neonates and prelabor rupture of membranes (PROM) were evaluated using Risk Ratios (95%CI) and Population Attributable Risk Fractions. RESULTS: PD was associated with a higher risk of PTB (RR(adj. )3.47 95%CI 1.62-7.43), LBW (RR(adj. )2.93 95%CI 1.36-6.34) and PROM (RR(adj. )2.48 95%CI 1.35-4.56), but not with SGA neonates (RR 2.38 95%CI 0.93 - 6.10). CONCLUSIONS: PD was a risk factor for PT, LBW and PROM among Brazilian low risk pregnant women.